Hubungan lingkar perut dengan kadar gula darah puasa pada mahasiswa Fakultas Kedokteran Universitas Udayana angkatan 2014 - Alvin Wijaya; Nyoman Wande; Ida Ayu Putri Wirawati (Intisari Sains Medis, 2019)
Introduction: Diabetes Mellitus is a metabolic disease characterized by elevated blood sugar levels, either caused by a disturbance of insulin secretion, insulin resistance or both. Obesity is one of the risk factors of diabetes mellitus. The incidence of diabetes mellitus increases from year to year, but the data that discusses the association of risk factors with diabetes mellitus itself, especially obesity is minimum. The purpose of this study is to determine the association of abdominal circumference with fasting blood sugar levels at students of Udayana University Faculty of Medicine class of 2014.Method: This research is an analytical research conducted at Udayana University Faculty of Medicine Campus, Denpasar. Data obtained in the form of primary data in the form of abdominal circumference to see the status of obesity and fasting blood sugar to see the status of diabetes mellitus. Data were analyzed using SPSS program.Result: The results showed that there was not significant negative association between abdominal circumference with fasting blood sugar levels at Udayana University, Faculty of Medicine students class of 2014. However, this association is not statistically significant because diabetes mellitus influenced by many factors other than obesity. In addition, it can be seen that the characteristics of the population did not describe the population of diabetes mellitus or obesity, thus affecting associations that have been described in some literature and the concept of author thinking. But indeed the association of anthropometric risk factors (abdominal circumference) has a greater value than other risk factors.Conclusion: There was a negative correlation between abdominal circumference and fasting blood sugar but not significant statistically